An Evaluation of One-year B.Ed. Program of Tribhuvan University - Sharma, Rom Nath (Lumbini Journal of Language and Literature, 2022)
The purpose of this study was to evaluate the significance of the one-year B.Ed. course using Stufflebeam’s CIPP evaluation model (1983).This study focused on the thorough evaluation of the courses of one-year B.Ed. program launched by Tribhuvan University, Nepal. The courses were examined and evaluated from the perspective of the teachers who taught at one-year B.Ed. program and the students who completed the one-year B.Ed. The finding was that despite it is useful for the students who have planned to build up their career in teaching, the evaluation and assessment process were not effective. Four participants were selected to collect the data. They were two lecturers who taught at one-year B.Ed. Program at a constitutional campus of Tribhuvan University of Rupandehi District, Lumbini Province, Nepal and two students who studied and completed this program from the same campus. Data were collected through the interview based on the interview guidelines prepared on the basis of the CIPP evaluation checklist. This study is delimited to the courses offered to the students pursuing specializing English Language in one - year B.Ed. program.